154k views
3 votes
Find an equation tangent to the curve at the given point. 1. x²y+xy²=3x @ (-1,1)

1 Answer

2 votes

Compute
(\mathrm dy)/(\mathrm dx) via implicit differentiation:


x^2y+xy^2=3x\implies(\mathrm d)/(\mathrm dx)[x^2y+xy^2]=(\mathrm d)/(\mathrm dx)[3x]


(\mathrm d)/(\mathrm dx)[x^2y]+(\mathrm d)/(\mathrm dx)[xy^2]=3


\left((\mathrm d)/(\mathrm dx)[x^2]y+x^2(\mathrm d)/(\mathrm dx)[y]\right)+\left((\mathrm d)/(\mathrm dx)[x]y^2+x(\mathrm d)/(\mathrm dx)[y^2]\right)=3


\left(2xy+x^2(\mathrm dy)/(\mathrm dx)\right)+\left(y^2+2xy\,(\mathrm dy)/(\mathrm dx)\right)=3


(x^2+2xy)(\mathrm dy)/(\mathrm dx)=3-2xy-y^2


(\mathrm dy)/(\mathrm dx)=(3-2xy-y^2)/(x^2+2xy)

The value of
(\mathrm dy)/(\mathrm dx) at any point
(x,y) on the given curve is the slope of the line tangent to it at this point. So at (-1, 1), we get


(\mathrm dy)/(\mathrm dx)=-4

Then the equation of this tangent line is


y-1=-4(x-(-1))\implies y=-4x-3

User Csf
by
5.3k points